Towards the anti-fibrillogenic activity of phthalocyanines with out-of-plane ligands: correlation with self-association proneness - Kovalska, V.B.; Losytskyy, M.Yu.; Chernii, S.V.; Chernii, V.Ya.; Tretyakova, I.M.; Yarmoluk, S.M.; Volkov, S.V. (Вiopolymers and Cell, 2013)
Aim. The activity of five hafnium phthalocyanines containing out-of-plane ligands as inhibitors of reaction of insulin fibril formation is studied and correlation between their inhibitory properties and tendency to self-association is discussed. Methods. Fluorescence and absorption spectroscopy. Results. For the complexes with weak proneness to self-association PcHfDbm2, PcHfPyr2, and PcHfBtfa2 the values of inhibitory activity were estimated as 60–73 %. For phthalocyanines with the pronounced tendency to self-association PcHfPiromelit and PcHfCl2 the noticeably higher inhibitory activity values (about 95 %) were shown. In the presence of native or fibrilar insulin the destruction of self-associates of metal complex occurs in buffer pH 7.9, Besides upon the conditions of insulin fibrillization reaction (0.1 M HCl) phthalocyanines exist predominantly as monomers. Conclusions. The phthalocyanines with out-of-plane ligands with higher tendency to self-association have shown higher inhibitory activity in the insulin fibril formation comparing with the poorly aggregated metal complexes. At the same time low-order self-associates are not involved directly in the mechanism of inhibition of insulin fibrillization and the phthalocyanines bind with protein in monomeric form. Tendency of phthalocyanines to self-association in aqueous media seems to be an «indicator» of their proneness to stack with protein aromatic amino-acids and thus of anti-fibrilogenic properties. Мета. Дослідити активність п’яти фталоціанінів гафнію, що містять позаплощинні ліганди як інгібітори реакції фібрилоутворення інсуліну, та встановити кореляцію між інгібіторними властивостями фталоціанінів і їхньою схильністю до самоасоціації. Методи. Флуоресцентна спектроскопія і спектроскопія електронного поглинання. Результати. Для комплексів PcHfDbm2, PcHfPyr2 і PcHfBtfa2, які практично не утворюють агрегатів у водному буфері, інгібіторна активність становить 60–73 %. Фталоціаніни PcHfPiromelit і PcHfCl2 з високою схильністю до утворення агрегатів практично повністю пригнічують формування амілоїдних фібрил інсуліну (інгібіторна активність приблизно 95 %). У водному буфері за присутності мономерного або фібрилярного інсуліну відбувається руйнування агрегатів металокомплексів. Крім того, за умов проведення реакції фібрилізації інсуліну (0,1 М HCl) фталоціаніни існують переважно у вигляді мономерів. Висновки. Фталоціаніни з позаплощинними лігандами з тенденцією до самоасоціації демонструють вищу інгібувальну активність у реакції фібрилізації інсуліну порівняно з металокомплексами, які агрегують гірше. Фталоціанінові самоасоціати низького порядку безпосередньо не залучені до механізму інгібування агрегатоутворення інсуліну, тобто фталоціанін зв’язується з білком у мономерній формі. Тенденцію до самоасоціації фталоціані- нів у водному середовищі можна розглядати як «індикатор» їхньої схильності до взаємодії з ароматичними амінокислотами і, отже, як показник їхньої антифібрилогенної активності. Цель. Исследовать активность пяти фталоцианинов гафния, содержащих внеплоскостные лиганды в качестве ингибиторов реакции фибриллообразования инсулина, и установить корреляцию между их ингибиторными свойствами и склонностью к самоассоциации. Методы. Флуоресцентная спектроскопия и спектроскопия электронного поглощения. Результаты. Для комплексов PcHfDbm2, PcHfPyr2 и PcHfBtfa2, практически не образующих агрегатов в водном буфере, ингибиторная активность составляет 60–73 %. Фталоцианины PcHfPiromelit и PcHfCl2 с высокой склонностью к образованию агрегатов практически полностью подавляют формирование амилоидных фибрилл инсулина (ингибиторная активность около 95 %). В водном буфере в присутствии мономерного или фибриллярного инсулина происходит разрушение агрегатов металлокомплексов. Кроме того, в условиях проведения реакции фибриллизации инсулина (0,1 М HCl) фталоцианины существуют преимущественно в виде мономеров. Выводы. Фталоцианины с внеплоскостными лигандами с тенденцией к самоассоциации демонстрируют высокую ингибирующую активность в реакции фибриллизации инсулина по сравнению с металлокомплексами, агрегирующими хуже. Фталоцианиновые самоассоциаты низкого порядка непосредственно не вовлечены в механизм ингибирования агрегатообразования инсулина, т. е. фталоцианин связывается с белком в мономерной форме. Тенденцию к самоассоциации фталоцианинов в водной среде можно рассматривать как «индикатор» их склонности ко взаимодействию с ароматическими аминокислотами и, следовательно, как показатель их антифибриллогенной активности.